Katherine Mansfield: The Horror of Femininity - Chowdhury, Mohammad Shahidul Islam (EAST WEST JOURNAL OF HUMANITIES, 2017)
This paper focuses on the theme of femininity, in the short stories of Katherine Mansfield (1888 – 1923), as causative for horror in a Modernist mood. As Mansfield disseminates gender-performance from its periphery towards a thematic whole within the reality of domesticity during the fragmented modern period, she focuses on how feminine consciousness works in an individual, and how that consciousness germinates a self that voices itself in adverse circumstances. By propagating the self, she unveils a darker realization of it: horror. This horror works as a dismantling force in the female characters of her stories that tell of their suffering, experience, and helplessness, which eventually reveal the horror they encounter throughout their existence. Mansfield’s can be treated as an exposure of her own experience in the modernist environment. The shock she went through as an author is also exemplified in her writings. The characters unearth their observance, which is the attenuation of self through horror. In this way, Mansfield gleans the topic of femininity as an individual experience of horror. This paper aims to find how Mansfield presents the horror of femininity as a comprehensive mood of modernism in her short stories.]